Knowledge and Assitude of Mothers who have Children under Life about Giving Vitamin A to Children under Life at Posyandu Sayang Balita Ujung Batu Subdistrict Working Area in Puskesmas Ujung Batu Period April â Mey 2010 - SEPDUWIANA, HENY; -, MERI (Jurnal Martenity and Neonatal, 2012)
The Background of 20 million chidren under five in Indonesia, at the age 6 months to 5 years ole half of othem suffer from lack of Vitamin A. Indonesia is one country in Asia that the level of vitamin A complience with a relatively low. This problem can be caused by society low level of Knowledge and assitude to word the importance of vitamin A to children under five.